1990
DOI: 10.1107/s010876818901308x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal packing of hydrocarbons. Effects of molecular size, shape and stoichiometry

Abstract: 275practically completely explained in terms of modulations of the average structure which are of the £2 symmetry, even though the average crystal structure corresponds to a frozen-in £, modulation.We argue that the short-range order, which tends locally to preserve the c-glide plane, is due to dipoledipole interactions between molecules. On the other hand, the stability of the lattice over a long range (corresponding to wavevectors close to q = 0) is governed by the short-range repulsive interactions and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 14 publications
(22 reference statements)
2
9
0
Order By: Relevance
“…Kitaigorodskii’s analysis of known molecular crystal structures revealed that most aromatic molecules exhibit a packing coefficient between 0.6 and 0.8, a range that was later corroborated using database analyses and statistical methods . Orelkin ( c .…”
Section: The Nature Of the Molecular Crystalmentioning
confidence: 94%
See 1 more Smart Citation
“…Kitaigorodskii’s analysis of known molecular crystal structures revealed that most aromatic molecules exhibit a packing coefficient between 0.6 and 0.8, a range that was later corroborated using database analyses and statistical methods . Orelkin ( c .…”
Section: The Nature Of the Molecular Crystalmentioning
confidence: 94%
“…Kitaigorodskii's analysis of known molecular crystal structures revealed that most aromatic molecules exhibit a packing coefficient between 0.6 and 0.8, a range that was later corroborated using database analyses and statistical methods. 59 Orelkin (c. 1930) proposed that densely packed molecular crystals are obtained when the "bumps" of one molecule are inserted in the "hollows" of the neighboring molecule, 50 whereby intermolecular contacts are maximized and void spaces are minimized. The importance of complementary molecular surfaces was also emphasized in 1940 by Pauling and Delbruck.…”
Section: The Nature Of the Molecular Crystalmentioning
confidence: 99%
“…An in-depth overview of computational chemistry in the context of crystal engineering is beyond the scope of this article. Several authors have outlined many of the possibilities and challenges of theoretical supramolecular chemistry (Gavezzotti, 1990;Gavezzotti & Filippini, 1995, 1996Holden, Du & Ammon, 1993;. Gavezzotti (1994) asked the crucial question in a recent review, 'Are crystal structures predictable', and the current answer would have to be 'Sometimes'.…”
Section: Function and Futurementioning
confidence: 99%
“…Qufmica desire to use "engineered" ligands for specific applications in coordination chemistry, the second one is related to the importance of separating the intrinsic properties of molecules, including their geometries, from the consequences of intermolecular interactions in the solid state. Only this approach will allow the determination of crystal packing effects [8,9].…”
Section: Introductionmentioning
confidence: 99%